2020
DOI: 10.1057/s41287-020-00279-8
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Technical Efficiency in the Presence of Developments Toward Commercialization: Evidence from Tanzania’s Milk Producers

Abstract: The level and determinants of technical efficiency in milk-producing households are examined in connection with households’ level of commercialization. A sample of 469 milk producers are modeled using Stochastic Frontier Analysis (SFA). Average Technical Efficiency (TE) is estimated to be 80%, with variation among regions and generally reflecting levels of commercialization. Results show that assuming milk producers are rational, TE is increased by increasing the number of cattle, cows, and crossbreeds, and by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Other differences such as soil quality, temperature, and rainfall can also be expected [16,17]. Regional differences have also been noted by Batha et al [18].…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Other differences such as soil quality, temperature, and rainfall can also be expected [16,17]. Regional differences have also been noted by Batha et al [18].…”
Section: Discussionmentioning
confidence: 64%
“…The positive relationship between herd size and efficiency was also confirmed by Demircan [50]. According to Batha et al [18], technical efficiency increases with an increasing number of cattle. Priyanka et al [21] showed that technical efficiency was high for all herd size categories.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The outcome variable for Phase I's SFA is liters of milk produced, captured in surveys as the total volume of milk produced on-farm in the prior year. Explanatory variables for analyzing dairy productivity with SFA typically include: farmer characteristics such as age, education, and years of experience; cow herd size and breed type; measures of labor; inputs such as feed and veterinary costs; climate data; water availability; access to markets, credit, and extension services; and household size (Masuku and Sihlongonyane, 2015;Masunda and Chiweshe, 2015;Nakanwagi and Hyuha, 2015;Hassan et al, 2018;Girma, 2019;Bahta et al, 2021). Unfortunately, the available dataset did not include climate data on temperature or rainfall, nor variables reflecting water availability or extension services, but other variables mentioned were available for testing in the frontier and the inefficiency model.…”
Section: Dependent and Predictor Variables For Phase Imentioning
confidence: 99%
“…Jan et al [37], when assessing the long-term technical efficiency of Swiss dairy farms located in mountain areas, while taking into account both social, economic and environmental resources, have shown that technical efficiency is positively influenced by: farm size, a focus on non-agricultural income, milk production intensity and ecological production system, and that negative impacts on the technical efficiency of dairy farms are: part-time work, off-farm work, intensity of feed and concentrate use, age and education of the farmer. Bahta et al [38], by analyzing the level and determinants of technical efficiency on dairy farms in Tanzania with the use of SFA, have proven that increasing the number of cattle, additional veterinary and fodder inputs increase the technical efficiency of dairy farms. The efficiency of dairy farms also improves access to credit, training, and membership in producer groups.…”
Section: Literature Reviewmentioning
confidence: 99%